PEMANFAATAN LIMBAH PENGGERGAJIAN KAYU SENGON (Paraserianthes falcataria) MENJADI PAPAN SERAT - Sufi, Efrina Fathya; Susdiyanti, Tun; Meiganati, Kustin Bintani (Jurnal Nusa Sylva, 2018)
Fiberboard can be made from a variety of berligno-cellulose fiber materials. One of the berligno-sesulose fiber materials is Sengon wood which is a waste of sawmills. Efforts to use sengon wood waste can be used for high density fiberboard. In this study we want to see the quality of sengon wood fiber board with TRF adhesive (Tanin Resolsinol Formaldehyde). The sengon wood fiber board was tested according to the JIS A-5905-2003 standard. The parameters tested were the physical-mechanical quality of the fiberboard, namely density, moisture content, water absorption, thickness development, elastic modulus, fracture modulus and internal adhesive strength. TRF is applied in three levels, namely: 0%, 6% and 8%. The results showed that the physical-mechanical quality that met the JIS A-5905-2003 standard was density (0.935 - 1.204 g / cm3), moisture content (9.840 - 12.2%), modulus of elasticity (313.55 - 355.53 kg / cm2), broken modulus (36,672 - 39,341 kg / cm2) and internal adhesion strength (4,244 - 4,371 kg / cm3). While the nature of water absorption (65,875 - 79,856%) and the development of thickness (27,665 - 39,295%) did not meet the JIS A-5905-2003 standard, at all TRF levels.